Elevated plasma levels of the appetite-stimulator ACBP/DBI in fasting and obese subjects - Li, Sijing (Cell Stress, 2021)
Eukaryotic cells release the phylogenetically ancient protein acyl coenzyme A binding protein (ACBP, which in humans is encoded by the gene DBI, diazepam binding inhibitor) upon nutrient deprivation. Accordingly, mice that are starved for one to two days and humans that undergo voluntary fasting for one to three weeks manifest an increase in the plasma concentration of ACBP/DBI. Paradoxically, ACBP/DBI levels also increase in obese mice and humans. Since ACBP/DBI stimulates appetite, this latter finding may explain why obesity constitutes a self-perpetuating state. Here, we present a theoretical framework to embed these findings in the mechanisms of weight control, as well as a bioinformatics analysis showing that, irrespective of the human cell or tissue type, one single isoform of ACBP/DBI (ACBP1) is preponderant (~90% of all DBI transcripts, with the sole exception of the testis, where it is ~70%). Based on our knowledge, we conclude that ACBP1 is subjected to a biphasic transcriptional and post-transcriptional regulation, explaining why obesity and fasting both are associated with increased circulating ACBP1 protein levels.